Answer:
Step-by-step explanation:
Answer:
3
Step-by-step explanation:
We know x = -2, so we can substitute -2 in for x
3x^2- 9
3*-2^2-9
Solve the exponent first (PEMDAS)
3*4-9
Multiply next
12-9
Subtract
3
0.50x-6=4
move -6 to the other side
sign changes from -6 to 6
0.50x-6+6= 4+6
0.50x= 10
divide by 0.50 for both sides
0.50/0.50x= 10/0.50
x= 20
Answer: x= 20
To solve this problem, we must first convert the distance
into miles:
distance = 60 ft (1 mile / 5280 ft) + 6 inches (1 foot /
12 inches) (1 mile / 5280 ft)
distance = 0.0114583 mile
To calculate for time:
time = distance / speed
time = 0.0114583 mile / (90 miles / 3600 seconds)
time = 0.458 seconds
<span>time = 0.46 seconds</span>
Answer:
![(2,\infty)](https://tex.z-dn.net/?f=%282%2C%5Cinfty%29)
Step-by-step explanation:
After x=2, we see that the change in y over the change in x is positive since both variables increase with each other, so
is where the function is increasing.